2018
DOI: 10.1002/jobm.201700529
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesized silver nanoparticles demonstrating enhanced in vitro and in vivo antibiofilm activity against Candida spp.

Abstract: Candida species are opportunistic fungal pathogens, which are known for their biofilm associated infections on implanted medical devices in clinical settings. Broad spectrum usage of azole groups and other antifungal agents leads to the occurrence of drug resistance among Candida species. Most of the antifungal agents have failed to treat the biofilm mediated Candida infections. In the present study, silver nanoparticles (AgNPs) were synthesized using Dodonaea viscosa and Hyptis suoveolens methanolic leaf extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 68 publications
2
22
0
1
Order By: Relevance
“…We note that the AgNPs IC50 value for the C. auris AR #0390 strain is higher than the value reported for the same strain as reported by Lara et al (1.1 μg mL -1 vs 0.06 μg mL -1 , respectively), which is most likely related to the different techniques used for the synthesis of these nanoantibiotics resulting in AgNPs with different characteristics. Also, the antibiofilm activity of our AgNPs is comparable to the activity described for AgNPs synthesized using different methods against other Candida species [29,34,35].…”
Section: Resultssupporting
confidence: 72%
“…We note that the AgNPs IC50 value for the C. auris AR #0390 strain is higher than the value reported for the same strain as reported by Lara et al (1.1 μg mL -1 vs 0.06 μg mL -1 , respectively), which is most likely related to the different techniques used for the synthesis of these nanoantibiotics resulting in AgNPs with different characteristics. Also, the antibiofilm activity of our AgNPs is comparable to the activity described for AgNPs synthesized using different methods against other Candida species [29,34,35].…”
Section: Resultssupporting
confidence: 72%
“…from 79 to 88% at 10 µg/mL. 52 Monteiro et al 53 reported that colloidal suspensions of AgNPs at 54 μg/mL inhibit the biofilm formation approximately 54 and 90% in C. albicans and C. glabrata, respectively. The exact mechanism of inhibition of biofilm formation by AgNPs is not known.…”
Section: Visualization Of C Albicans Biofilm By Congo Red Agar and Clsmmentioning
confidence: 99%
“…However, cells treated with ScAgNPs not only inhibit the production of exopolysaccharides, but also inhibit the growth of cells ( Figure S1). Muthamil et al 52 reported that AgNPs strongly inhibit the EPS production in C. albicans, C. glabrata,and C. tropicalis. The visualization and quantification of biofilm and distribution of live and dead cells after treatment of ScAgNPs were evaluated by CLSM using LIVE/DEAD biofilm viability florescent stains, ie, ConA-FITC and PI.…”
Section: Visualization Of C Albicans Biofilm By Congo Red Agar and Clsmmentioning
confidence: 99%
“…AgNPs can also impart their antibacterial activity through the interaction and interruption of the macromolecules function such as DNA and enzyme by mechanism such as a free-radical production or electron release. AgNPs produced using the EPS secreted from B. subtilis has shown an effective inhibition against bacterial growth, with greater efficiency toward gram-negative than grampositive bacteria [61]. These types of AgNPs synthesized from bacteria secreted ESP have shown successful inhibition activity against microorganisms such as P. aeruginosa, S. aureus, B. cereus, E. coli, and P. vulgaris [62,63].…”
Section: Antimicrobial Properties Of Polysaccharide-based Agnpsmentioning
confidence: 99%